A Systematic Literature Review: Podcast as Teaching Media to Improve Listening Skill: English - Iwan Setiawan; Sri Wahyuni (Prodi Tadris Bahasa Inggris, 2024)
Instructional media has essential role for teaching and learning English listening skills. By implementing appropriate media, such as podcasts, into learning process, teachers can raise students’ performance and create a more productive learning environment. The increasing amount of empirical research examining podcasts as instructional tools for enhancing listening comprehension has grown intriguing. This research method uses the PRISMA method which consisted three steps: identification, screening and eligibility. This review explored 20 eligible studies and synthesized results related to two keys aspects the implementation of the podcast and the effectiveness of the podcast on listening skill. The result asserted positive findings regarding the utilization of podcasts to enhance students’ listening skills. Podcasts were implemented at different education levels across countries and regions. All included studies reported that podcasts were effective in increasing students’ listening skills. The findings of this review contribute to creating effective teaching media and gaining better learning outcomes.